Advanced health telematics and telemedicine: The Magdeburg expert summit textbook - Blobel, Bernd (IOS, 2013)
In this publication, leading experts present all the different aspects of practically enabling advanced health telematics and telemedicine. Some examples are: architectural issues, electronic health records, communication, security and safety as well as the legal and ethical implications. Also discussed in more detail are the results of international collaboration, ongoing efforts and future directions. The book is of interest to health professionals, computer scientists, lawyers and politicians, as well as developers, users and decision-makers.